A greener and efficient access to substituted four- and six-membered sulfur-bearing heterocycles. Issue 23 (1st June 2017) - Parisi, Giovanna; Degennaro, Leonardo; Carlucci, Claudia; de Candia, Modesto; Mastrorilli, Piero; Roller, Alexander; Holzer, Wolfgang; Altomare, Cosimo Damiano; Pace, Vittorio; Luisi, Renzo
Abstract : The regioselective functionalization of four- and six-membered cyclic sulfones was investigated using a lithiation/functionalization strategy. Abstract : The regioselective functionalization of four- and six-membered cyclic sulfones was investigated using a lithiation/electrophile trapping strategy. The protocol features an interesting eco-compatibility profile because of the use of 2-MeTHF as a solvent (more eco-friendly than other organic solvents) and n -hexyllithium as a lithiating agent safer than other alkyllithium compounds. Several derivatives were prepared with different stereochemistry and substitution patterns. A number of selected derivatives, spanning a range of 5 log P units, were characterized for their lipophilicity through RP-HPLC. A good linear correlation, with a slope close to 1.0, was observed between the experimentally determined RP-HPLC lipophilicity parameters (log k ′w ) and calculated log P (clog P ) values, whereas a systematic difference in absolute values between the chromatographic parameters and in silico lipophilicity descriptors can be attributed mainly to silanophilic interactions between the H-bond acceptor SO2 group and free silanol groups on silica-based C18 columns, which results in increased retention times.